Representation of Gendered Identities in Contemporary Indian English Drama: A Study of Mahesh Dattani’s Plays, Tara and Dance Like a Man - Bharathi S. Rai; Vinil Rohan D’Souza (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Mahesh Dattani stands as one of the most significant voices in contemporary Indian English drama, particularly for his bold engagement with marginalized identities and socially silenced issues. Among the most persistent concerns in his dramatic oeuvre is gender - its construction, performance, and the systemic inequalities it produces. This research paper examines gender perspectives in two of Dattani’s most critically acclaimed plays, Tara (1990) and Dance Like a Man (1989). Through a close textual and thematic analysis, the study explores how patriarchal norms shape individual identities, familial relationships, and social expectations, often resulting in psychological trauma and emotional alienation. Tara foregrounds gender discrimination within the family structure, revealing how female children are systematically devalued even by women themselves. The play exposes the internalization of patriarchy and critiques the cultural preference for male heirs through the tragic fate of the female protagonist. In contrast, Dance Like a Man interrogates gender roles by challenging traditional notions of masculinity and femininity, particularly through the lens of classical dance - a space culturally marked as feminine. The male protagonist’s struggle to assert his identity as a dancer highlights the rigid boundaries imposed by hegemonic masculinity. By situating these plays within feminist and gender theory, this paper argues that Dattani does not merely depict gender inequality but actively destabilizes normative gender binaries. His characters resist, negotiate, and sometimes succumb to social prescriptions, making gender a dynamic and contested site. Ultimately, the study demonstrates that Dattani’s drama functions as a powerful critique of patriarchal ideology in Indian society while advocating for individual freedom and gender inclusivity.